2016
DOI: 10.1111/vop.12374
|View full text |Cite
|
Sign up to set email alerts
|

Scleral and corneal xanthomatous inflammation in a gray mouse lemur (Microcebus murinus)

Abstract: Bilateral multifocal corneal opacity was detected in a 4.5-year-old male captive gray mouse lemur (Microcebus murinus) without other clinical ocular changes. Histopathological examination revealed a severe diffuse granulomatous scleritis and focal keratitis with intralesional cholesterol, consistent with xanthomatous inflammation. This is the first report of xanthomatous inflammation in a gray mouse lemur. This condition may be the result of systemic factors (lipid metabolism disorders) and/or local predisposi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…However, although these results have been observed in humans as well as other non-human primates and rodents (Vitiello et al, 1986; Czeisler et al, 1992; Valentinuzzi et al, 1997; Weinert et al, 2000; Weinert and Waterhouse, 2007; Zhdanova et al, 2011; Duffy et al, 2015), they do not explain whether these observed age-related alterations are due to a reduction of sensitivity to external light factors or to changes within the clock mechanism itself. However, a high incidence of ocular pathologies has been identified in mouse lemurs that are older than 7 years (Beltran et al, 2007; Alleaume et al, 2017; Dubicanac et al, 2017). This strongly suggests a decrease in light responsiveness through filtering of short wavelengths that are known to be efficient in the synchronization of daily rhythms in mouse lemurs (Gomez et al, 2012).…”
Section: Evolution Of the Circadian Pacemaker Over The Lifetime: Effementioning
confidence: 99%
“…However, although these results have been observed in humans as well as other non-human primates and rodents (Vitiello et al, 1986; Czeisler et al, 1992; Valentinuzzi et al, 1997; Weinert et al, 2000; Weinert and Waterhouse, 2007; Zhdanova et al, 2011; Duffy et al, 2015), they do not explain whether these observed age-related alterations are due to a reduction of sensitivity to external light factors or to changes within the clock mechanism itself. However, a high incidence of ocular pathologies has been identified in mouse lemurs that are older than 7 years (Beltran et al, 2007; Alleaume et al, 2017; Dubicanac et al, 2017). This strongly suggests a decrease in light responsiveness through filtering of short wavelengths that are known to be efficient in the synchronization of daily rhythms in mouse lemurs (Gomez et al, 2012).…”
Section: Evolution Of the Circadian Pacemaker Over The Lifetime: Effementioning
confidence: 99%
“…Indeed, mouse lemurs have been proposed as a model of primate aging and Alzheimer’s disease because 5–20% of adults over age 5 in one colony show signs of premature aging, including brain atrophy, amyloid plaques, and cytoskeletal Tau pathology, accompanied by cognitive and social decline (Bons et al 2006; Languille et al 2012). Mouse lemurs are also susceptible to a variety of tumors (Remick et al 2009) and eye diseases (Beltran et al 2007; Alleaume et al 2017). …”
Section: Mouse Lemur An Excellent Candidate For a Primate Genetic Momentioning
confidence: 99%